A Critical Discourse Analysis of some Selected Newspaper Reports about Yemen Conflict - Abass Hamoud , Hamed; Al Mawla, Fida (Journal of College of Education, 2021)
The present paper aims at conducting a Critical Discourse Analysis analysis of the reports of two newspapers, namely, Tehran Times and Asharq Al-Awsat about Yemen conflict. The present paper is mainly limited to the critical discourse analysis of the newspaper reports that tackle Yemen war from March 2015 to December 2016. The study aims at Figure out whether or not there is a clear bias in the reports of these two newspapers. The paper conducts both a qualitative and a quantitative discourse analysis depending on Van Dijk’s “Ideological Square” (2000). The analysis of the reports of the two newspapers reveals that the reports are not free from bias. Both newspapers organize their reports in a way in which the ‘in-group’ and ‘out-group’ are polarized.
Keywords: Yemen war, Ideological Square, bias